The willingness to participate in biomedical research involving human beings in low‐ and middle‐income countries: a systematic review - Browne, Joyce L.; Rees, Connie O.; Delden, Johannes J. M.; Agyepong, Irene; Grobbee, Diederick E.; Edwin, Ama; Klipstein‐Grobusch, Kerstin; Graaf, Rieke (Tropical medicine & international health, 2019)
Objectives To systematically review reasons for the willingness to participate in biomedical human subjects research in low‐ and middle‐income countries (LMICs). Methods Five databases were systematically searched for articles published between 2000 and 2017 containing the domain of ‘human subjects research’ in ‘LMICs’ and determinant ‘reasons for (non)participation’. Reasons mentioned were extracted, ranked and results narratively described. Results Ninety‐four articles were included, 44 qualitative and 50 mixed‐methods studies. Altruism, personal health benefits, access to health care, monetary benefit, knowledge, social support and trust were the most important reasons for participation. Primary reasons for non‐participation were safety concerns, inconvenience, stigmatisation, lack of social support, confidentiality concerns, physical pain, efficacy concerns and distrust. Stigmatisation was a major concern in relation to HIV research. Reasons were similar across different regions, gender, non‐patient or patient participants and real or hypothetical study designs. Conclusions Addressing factors that affect (non‐)participation in the planning process and during the conduct of research may enhance voluntary consent to participation and reduce barriers for potential participants. Objectifs Analyser systématiquement les raisons de la volonté de participer à la recherche biomédicale sur les sujets humains dans les PRFI. Méthodes Cinq bases de données ont été systématiquement recherchées pour des articles publiés entre 2000 et 2017 contenant le domaine de la «recherche sur des sujets humains» dans les «PRFI» et les déterminantes «raisons de la (non) participation». Les raisons mentionnées ont été extraites, classées et les résultats décrits de manière narrative. Résultats 94 articles ont été inclus, 44 études qualitatives et 51 études à méthodes mixtes. L'altruisme, les avantages pour la santé personnelle, l'accès aux soins de santé, les avantages pécuniaires, les connaissances, le soutien social et la confiance étaient les principales raisons de la participation. Les principales raisons de la non‐participation étaient les problèmes de sécurité, les inconvénients, la stigmatisation, le manque de soutien social, les soucis de confidentialité, la douleur physique, les soucis d'efficacité et la méfiance. La stigmatisation était une préoccupation majeure dans le cadre de la recherche sur le VIH. Les raisons étaient similaires dans les différentes régions, le sexe, les participants patients ou non‐patients et les modèles d’étude réels ou hypothétiques. Conclusions La prise en compte des facteurs qui affectent la (non) participation au processus de planification et au cours de la recherche peut renforcer le consentement volontaire à la participation et réduire les obstacles pour les participants potentiels.